Aplicação do método lagrangiano SPH (Smoothed Particle Hydrodynamics ) para a solução do problema das cavidades - Pinto, Wesley José Nunes (2013)
In this study, it was applied the numerical method, grid-free, based on particles named SPH (Smoothed Particles Hydrodynamics). Also, a numerical code in the computer language FORTRAN was used to solve the Navier-Stokes Equations. This classic problem of the literature related to Computational Fluid Dynamics indicated as Shear-Driven Cavity Flow was studied to check the behavior of the numerical code regarding specific existing results. Such problem is highly used as Benchmark, aiming the validation of the numerical method used to develop the research. The analysis and validation of the numerical code was divided into three sections: the first one lists the location of the centre of the main vortex generated by the flow of the upper edge of the cavities; the second one plots the profiles of the components of the central speed of the cavities; the third one lists the absolute deviation of the profiles of the central speed of this study compared with other cases data. It is established that the SPH Method presented accuracy in the performed simulations, in a consonance between the results of the dynamic simulations and the reference data, thus the proposed numerical model was validated with better results for low Reynolds numbers.